DIMENSI PSIKOLOGIS DAN SOSIAL DI BALIK TINDAK PEMBUNUHAN: KAJIAN SOSIOLOGI PERILAKU MENYIMPANG DI LAPAS CIPINANG - Ciek Julyati Hisyam; Alfia Zahra; Citra Khodijah Tri Andini; Miftahul Khairiah; Nabila Egy Siagian; Raihanun Ummu Salamah; Syakinah Syakinah; Shofiatunnisa Shofiatunnisa; Naila Nursyaluna Izzati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to thoroughly examine the psychological and social dimensions underlying the act of murder among inmates at Cipinang Penitentiary Institution (Lapas Cipinang), through the lens of the Sociology of Deviant Behavior. The study focuses on analyzing the complex interplay between internal factors and external factors that contribute to the decision and execution of such extreme criminal acts. Utilizing a qualitative approach with a case study at Lapas Cipinang, data was collected through in-depth interviews with convicted murderers and participant observation. The findings indicate that the act of murder is often the culmination of a series of social deviation processes triggered by a combination of emotional instability and failure of socialization. This study emphasizes the need for rehabilitation interventions that focus not only on legal sanctions but also on psychosocial restoration and the strengthening of social support structures as a more effective effort to prevent further deviant behavior.